Synthesis and biological evaluation of 1-acetyl-5-substituted aryl-3-(β-amino naphthyl) - 2-pyrazolines. - YAMINILATHA T; VARALAKSHMI DEVI K; RAJITHA G (International Journal of Pharma and Bio Sciences, 2017)
The pyrazoline is an important five membered heterocyclic ring system which has inspired many researchers to carry out structural variations in the ring, which has propelled the development of varied pyrazolines with an array of pharmacological activities. On the other hand naphthalene has been identified as a new range of potent antimicrobials effective against wide range of human pathogens. The present work is aimed to synthesize the novel derivatives of naphthalene substituted pyrazolines and to explore the potentiality of the derivatives as antioxidant and antibacterial activities. The intermediate β-amino naphthyl substituted chalcones were prepared by refluxing β-acetylamino naphthalene with various aromatic aldehydes in presence of NaOH. The intermediate is treated with hydrazine hydrate in presence of glacial acetic acid and ethanol to yield the title compounds 1-acetyl-5-substituted aryl-3-(β-aminonaphthyl)-2-pyrazolines (4a-j). The synthesized compounds were screened for their antibacterial activity against four strains of bacteria namely Bacillus subtilis and Staphylococcus aureus (gram-positive), Escherichia coli and Staphylococcus aureus (gram negative) by agar well diffusion method. The antioxidant activity was also evaluated by reduction of DPPH and Nitric oxide scavenging activity methods. Among the synthesized compounds, 4-methoxy (4c) derivative exhibited moderate activity against all the strains of the bacteria except towards Escherichia coli. 4-methoxy (4c), 3,4-dimethoxy (4d), 3,4,5-trimethoxy (4e) and 4-hydroxy (4j) derivatives showed moderate antioxidant activity.